Transcatheter aortic valve replacement versus surgical valve replacement in intermediate-risk patients: a propensity score analysis. Issue 10034 (28th May 2016) - Thourani, Vinod H; Kodali, Susheel; Makkar, Raj R; Herrmann, Howard C; Williams, Mathew; Babaliaros, Vasilis; Smalling, Richard; Lim, Scott; Malaisrie, S Chris; Kapadia, Samir; Szeto, Wilson Y; Greason, Kevin L; et al.
Summary: Background: Transcatheter aortic valve replacement (TAVR) with the SAPIEN 3 valve demonstrates good 30 day clinical outcomes in patients with severe aortic stenosis who are at intermediate risk of surgical mortality. Here we report longer-term data in intermediate-risk patients given SAPIEN 3 TAVR and compare outcomes to those of intermediate-risk patients given surgical aortic valve replacement. Methods: In the SAPIEN 3 observational study, 1077 intermediate-risk patients at 51 sites in the USA and Canada were assigned to receive TAVR with the SAPIEN 3 valve [952 [88%] via transfemoral access) between Feb 17, 2014, and Sept 3, 2014. In this population we assessed all-cause mortality and incidence of strokes, re-intervention, and aortic valve regurgitation at 1 year after implantation. Then we compared 1 year outcomes in this population with those for intermediate-risk patients treated with surgical valve replacement in the PARTNER 2A trial between Dec 23, 2011, and Nov 6, 2013, using a prespecified propensity score analysis to account for between-trial differences in baseline characteristics. The clinical events committee and echocardiographic core laboratory methods were the same for both studies. The primary endpoint was the composite of death from any cause, all strokes, and incidence of moderate or severe aortic regurgitation. We did non-inferiority (margin 7·5%) and superiority analyses in propensity score quintiles to calculate pooled weighted proportion differences for outcomes. Findings: At 1 year follow-up of the SAPIEN 3 observational study, 79 of 1077 patients who initiated the TAVR procedure had died (all-cause mortality 7·4%; 6·5% in the transfemoral access subgroup), and disabling strokes had occurred in 24 (2%), aortic valve re-intervention in six (1%), and moderate or severe paravalvular regurgitation in 13 (2%). In the propensity-score analysis we included 963 patients treated with SAPIEN 3 TAVR and 747 with surgical valve replacement. For the primary composite endpoint of mortality, strokes, and moderate or severe aortic regurgitation, TAVR was both non-inferior (pooled weighted proportion difference of −9·2%; 90% CI −12·4 to −6; p<0·0001) and superior (−9·2%, 95% CI −13·0 to −5·4; p<0·0001) to surgical valve replacement. Interpretation: TAVR with SAPIEN 3 in intermediate-risk patients with severe aortic stenosis is associated with low mortality, strokes, and regurgitation at 1 year. The propensity score analysis indicates a significant superiority for our composite outcome with TAVR compared with surgery, suggesting that TAVR might be the preferred treatment alternative in intermediate-risk patients. Funding: None.